ISOLASI DAN UJI TOKSISITAS SENYAWA ALKALOID DARI KULIT BATANG TUMBUHAN Polyalthia rumphii (B) Merr. (ANNONACEAE) - Hakim, Diski Rahman; Teruna, Hilwan Yuda; ', Yuharmen (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
An alkaloid has been isolated from the stem bark of Polyalthia rumphii and the toxicity activity was determined using the Brine Shrimp Lethality Test method againts larvae of Artemia salina Leach. The sample was extracted by maceration method using n-hexane and methanol respectively. The dried sample produced 4.19 g of n-hexane extract and 80.56 g of methanol extract. The methanol extract was extracted using acid-base method produced 0.04 g of crude alkaloids which then was subjected to column chromatography produced three fractions. Since the amount of fraction 1 & 3 was insufficient for further purification, only fraction 2 was purified using Sephadex LH-20 to give a compound coded as DK1. The structure of DK1 was determined using 1H-NMR spectroscopy and indicated that DK1 had aromatic rings and a methoxy group.The toxicity assay showed that the extract of methanol and the fraction 2 were toxic with LC50 154.98 and 243.91 ppm, respectively .